The Effect Of Giving Morage Leaf Extract For Increasing The Nutritional Status Of Toddlers - Hartina Atina; Selasih Putri Isnawati Hadi; Evy Ernawati (Universitas Malahayati Lampung, 2022)
ABSTRACT Nutrition is an important factor that aims to build quality human resources. Nutritional status in toddlers is very important in order to meet nutritional adequacy for growth and development. The impact of malnutrition on toddlers will cause stunting that it affects cognitive and intellectual abilities. Good nutritional status in toddlers according to Z-Score -2 SD - 2 SD. Moringa is a food that is rich in nutrients and can meet the needs of toddlers during the growth period. The nutritional value contained in Moringa is quite high, especially iron. Iron in 100 grams of Moringa leaves is 7 mg, when floured it becomes 28.2 mg. Besides being rich in iron, Moringa is also rich in protein, carbohydrates, calcium, vitamin C, and vitamin A. This study was to determine the effect of giving Moringa leaf extract to improve the nutritional status of toddlers. This type of research is Mixed Methods which combines quantitative and qualitative research methods. method Quantitative with Quasi Experiment design with Control Group Pretest and Posttest Design, method qualitative with the interview. The sampling technique of this study used random sampling on toddlers aged 1-3 years by taking into account the inclusion and exclusion criteria of 30 respondents. Data analysis using Wilcoxon Signed Rank Test. The results showed that the -value was 0.000 0.05, so it could be concluded that there was an effect of giving Moringa leaf extract on the nutritional status of toddlers based on weight according to height. There is an effect of giving Moringa leaf extract to improve nutritional status in toddlers. Keywords: Nutrition, Toddler, Moringa Leaf Extract ABSTRAK Gizi merupakan faktor penting yang bertujuan membangun sumber daya manusia yang berkualitas. Status gizi pada balita sangat penting agar memenuhi kecukupan gizi untuk pertumbuhan dan perkembangannya. Dampak kekurangan gizi pada balita akan menyebabkan stunting sehingga memengaruhi kemampuan kognitif dan intelektual. Status gizi yang baik pada balita menurut Z-Score -2 SD - 2 SD. Kelor merupakan bahan pangan yang kaya akan zat gizi dan dapat memenuhi kebutuhan balita selama masa pertumbuhan. Nilai gizi yang terdapat pada kelor cukup tinggi terutama zat besi. Zat besi dalam 100 gram daun kelor yaitu 7 mg, apabila ditepungkan menjadi 28,2 mg. Selain kaya akan zat besi, kelor juga kaya akan protein, karbohidrat, kalsium, vitamin C dan vitamin A. Tujuan penelitian ini adalah mengetahui pengaruh pemberian ekstrak daun kelor untuk peningkatan status gizi balita. Jenis penelitian ini adalah Mixed Methods yang mengabungkan metode penelitian kuantitatif dan kualitatif. Metode kuantitatif dengan desain Quasi Eksperiment dengan rancangan Control Group Pretest and Posttest Design, pada metode kualitatif dilakukan dengan interview. Teknik sampel penelitian ini menggunakan random sampling pada balita berusia 1-3 tahun dengan memperhatikan kriteria inklusi dan eksklusi sebanyak 30 responden. Analisis data menggunakan Wilcoxon Signed Rank Test. Hasil penelitian menunujukkan bahwa ρ-value sebesar 0,0000,05, maka dapat disimpulkan bahwa terdapat pengaruh pemberian ekstrak daun kelor terhadap status gizi balita berdasarkan berat badan menurut tinggi badan. Ada pengaruh pemberian ekstrak daun kelor untuk meningkatkan status gizi pada balita. Kata Kunci: Gizi, Balita, Ekstrak Daun Kelor